SOLUTIONS TO IMPROVE SUSTAINABLE PROJECTS APPLICATION OF SCIENCE AND TECHNOLOGY PROMOTION ECONOMIC DEVELOPMENT OF THE NORTH CENTRAL - Truong Thu Hang; Tran Anh Tuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2023)
In the context of a globalized economy, science and technology (S&T) is developing rapidly, the application of science and technology to socio-economic development, especially in agriculture in rural and mountainous areas. is absolutely necessary. The program “Support for the application and transfer of science and technology advances to serve the socio-economic development of rural and mountainous areas” (Rural and Mountainous Program) approved by the Prime Minister has gone through several stages (20 years of implementation) 1998-2002, 2004-2010, 2011-2015, 2016-2020 and is being implemented in the period 2021-2025, has contributed to the development of agricultural products with advantages of regions, forming applied enterprises hi-tech agriculture, improving management and technical skills for grassroots officials, creating jobs and increasing incomes for millions of farmers in rural and mountainous areas. Although many successes have been achieved, during the implementation process, there were also many difficulties in ensuring the sustainability of the projects (the project did not complete the task, did not maintain and replicate the model after completion of the project). end) - a very important factor that is decisive to the success of the Rural and Mountainous Program. In this article, the authors propose a number of solutions to improve the sustainability of the projects under the Rural and Mountainous Program through research in the North Central region. Code: 23020701